Cereal‐derived phenolic acids and intestinal alpha glucosidase activity inhibition: Structural activity relationship. Issue 6 (30th August 2018) - Malunga, Lovemore Nkhata; Joseph Thandapilly, Sijo; Ames, Nancy
Abstract: Phenolic acids are thought to be involved in modulating the activity of intestinal α‐glucosidase which is desirable in the treatment and management of diabetes. However, limited data exist on the structural activity relationship between phenolic acid derivatives and intestinal α‐glucosidase activity inhibition. Thus five (5) hydroxycinnamic and six (6) hydroxybenzoic acid derivatives and four (4) hydroxycinnamic acid conjugates common in cereal grains were used to investigate the structural activity relationship and the kinetics of enzyme inhibition. α‐Glucosidase activity was inhibited by 4%–55% in the presence of the phenolic acid derivatives. The inhibition potency was dependent on the number of hydroxyl and methoxy groups present in the aromatic ring. Conjugation to other compounds did not affect their inhibition potency. The Lineweaver–Burk plots suggest mixed, competitive and uncompetitive types of inhibition. These results suggest that some derivatives of phenolic acid could play a significant role in prevention and management of diabetes. Practical Applications: Phenolic acids, a group of biologically active compounds, present in cereal grains are thought to be involved in the prevention and management of diabetes through inhibiting the activities of enzymes in the intestine (such as α‐glucosidase). Intestinal α‐glucosidase is one of the enzymes required to breakdown sugars before their absorption into blood. This work investigated how the structure of phenolic acids found in cereal grain affects the activity of this enzyme. The results suggest that the number of hydroxyl and methoxy groups present in the main structure of phenolic acid decides to what extent the activity of the enzyme (α‐glucosidase) is inhibited. Understanding of this structure–activity relationship will help in identifying the type or variety of cereal grain that has the highest efficacy in preventing or managing diabetes based on their phenolic acid profile.